Prophet of the myrtle grove an exposition of the prophecy of Zechariah - Tatford, Frederick Albert, 1901- (Worthing, UK Henry E. Walter, 1971)
Includes bibliographical references.
Brethren writer.
Keywords: Bible. O.T. Zechariah -- commentaries